A fisiologia do prazer no livro IX da República e os seus problemas - Conque, João Gabriel (ΠΗΓΗ/FONS, 2017)
This article intends to point out some problems arising from the physiological conception of pleasure presented by Plato in Republic Book IX. Initially, I will show how Plato addresses the theme of pleasure in the Gorgias, highlighting the role of a kind of nutritional physiology in such context. Next, we will see Plato returns to the theme of pleasure in the penultimate book of the Republic in a more comprehensive way since this dialogue provides examples beyond nutritional sphere. Although the extensive discussion on pleasure in the Republic mentions intellectual pleasures, it does not provide us an accurate description of them. One of problems for the correct under-standing of such types of pleasures concerns the controversial conception of psychic pleasures as a process of replenishment. Thus, in the last section, I will draw attention to frequent analogy body/soul in Plato’s thought in order to contribute to the discussions on pleasure in the Republic.